Clinical features and survival pattern of central nervous system leukemia in children with acute lymphoblastic leukemia - Hardiono D. Pusponegoro; Moeslichan M. Z.; Risma K. Kaban; Rulina Suradi; Endang Windiastuti (Paediatrica Indonesiana, 2001)
Infiltration of leukemic cells into the central nervous system (CNS) is one of the causes of neurological disorders in patients with acute lymphoblastic leukemia (ALL) that worsen the prognosis. This retrospective cohort study aimed to review the clinical manifestations of children with CNS leukemia, their survival pattern and the role of early CNS leukemial. The survival curve was developed by Kaplan-Meier method, while the comparison of survival curves was done with log-rank test. Among 128 new ALL patients, 23 (18.0%) patients suffered from CNS leukemia, while 13 (10.2%) suffered from early CNS leukemia and 10 (7.8%) suffered from relapsing CNS leukemia. CNS leukemia was more common in male, in those aged less than 2 years, in those with white blood cell (WBC) count above 50,000/Ã¬l, and in patients type FAB-L2 ALL. The clinical manifestations most commonly found were decrease of consciousness (61%), vomiting (48%), cranial nerve palsy (44%), seizures (39%), and headache (26%). Relapsing CNS leukemia was more common in high risk (12.5%) compared with standard risk leukemia (5.7%). Patients with early CNS leukemia had a lower survival rate than those without early CNS leukemia (p = 0.0005). The percentage of patients with early CNS leukemia surviving up to 3 years was 26%. We conclude that early CNS leukemia could cause low survival ALL patients.